Apontamentos sobre a solidão em Ante-Sala e Íntima Fuligem, de Astrid Cabral - (:unkn) unknown (Universidade Federal do Amazonas, 2023)
A study about loneliness in the work of contemporary Brazilian poet Astrid Cabral is proposed. To fulfill this objective, concepts are investigated, lyric and fiction are discussed, understanding them as poetic construction through paratexts and the corpus is analyzed: texts from the books Ante-sala (2007) and Íntima Fuligem (2017). Astrid brings together a set of poems, according to Neiza Teixeira, “fingered on notes of solitude”: death, pain, memory, absence, muteness. Thus, the research was conducted by the following guiding questions: how do lyricism and fiction dialogue in Astrid's poetics? What metaphors did Astrid Cabral create in her poems to poetize the subject? How does the theme of exile contribute to this recreation of reality? In search of answers, I followed Klein's reasoning (1974), because loneliness is a unique subject, but it has several aspects and different ways of being discussed. It can be basically understood from two points of view: the ontological and the sociological, according to Siqueira (2009). Also, types, factors and myths were determined, according to Fonseca (2018), Moreira (2019) and Ferraz (2018). In order to encompass postmodern society, I sought support in Freud (2019), Zygmunt Bauman and Karnal (2018). Loneliness as a symbolic experience was subsidized by Lacan (1998), where it is the presence of the absence of the other. In addition, I discussed other solitudes such as Essencial, by Maurice Blanchot and Povoada, by Mikhail Bakhtin. To discuss fiction, I considered the reflections of Walty (1999) and deepened the fictional analysis of paratextuality based on Genette (2009) and the essay “Astrid Cabral: the teacher speaks of the poet”, from the book by Allison Leão. For the metaphor approach, I relied mainly on the studies of Aristotle, Paul Ricoeur, George Lakoff and Mark Johnson. The focus is on the representation of the theme in Astrid's poetry, reading the works in dialogue with the theory of conceptual metaphor in opposition to the classical theory. In this way, we seek to trace the metaphors created by the author that serve as a basis for determining her poetic look on loneliness.
Notes on loneliness in Ante-Sala and Íntima Fuligem, by Astrid Cabral
Keywords: Ficção brasileira - Análise; Poesia brasileira - Crítica e interpretação; LINGUISTICA, LETRAS E ARTES; Astrid Cabral; Solidão; Metáfora; Lakoff e Johnson